Crystal structure of (2E)-1-(4-hydroxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one - Yesilyurt, Fatma; Aydin, Abdullah; Gul, Halise Inci; Akkurt, Mehmet; Ozcelik, Nefise Dilek (European Journal of Chemistry, 2018)
The compound, C16H14O3, (except H atoms) is almost planar [r.m.s. deviations for all non-H atoms = 0.001 Å] and the dihedral angle between the aromatic rings is 9.35 (7)°. In the crystal, molecules are linked by intermolecular O—H···O and C—H···O hydrogen bonds, forming a three-dimensional network structure. Furthermore, a weak π-π stacking interactions [centroid-to-centroid distance = 3.7055 (9) Å] contributes to the stabilization of the molecular packing. Crystal Data for C16H14O3 (M = 254.27 g/mol): Orthorhombic, space group Pbca (no. 61), a = 13.4563(16) Å, b = 11.4986(14) Å, c = 16.720(2) Å, V = 2587.1(5) Å3, Z = 8, T = 296(2) K, μ(MoKα) = 0.090 mm-1, Dcalc = 1.306 g/cm3, 61402 reflections measured (4.88° ≤ 2Θ ≤ 56.76°), 3240 unique (Rint = 0.0334, Rsigma = 0.0120) which were used in all calculations. The final R1 was 0.0438 (I≥2σ(I)) and wR2 was 0.1228 (all data).
Keywords: 16. Peace & justice; 3. Good health